Virtual 3-D Facial Reconstruction - Martin Paul Evison (Internet Archaeology, 2000)
Facial reconstructions in archaeology allow empathy with people who lived in the past and enjoy considerable popularity with the public. It is a common misconception that facial reconstruction will produce an exact likeness; a resemblance is the best that can be hoped for. Research at Sheffield University is aimed at the development of a computer system for facial reconstruction that will be accurate, rapid, repeatable, accessible and flexible. This research is described and prototypical 3-D facial reconstructions are presented. Interpolation models simulating obesity, ageing and ethnic affiliation are also described. Some strengths and weaknesses in the models, and their potential for application in archaeology are discussed.